Creating an Eco-Sustainable Community: the Role of Zakat - Mohd. Ma’sum Billah (Center of Strategic Studies (PUSKAS) BAZNAS, 2016)
According to Saud (1988) and Shad (1986), the institution of Zakat, is a divine obligatory sort of taxation acting as the most effective measure in upgrading the financial condition of the destitute. This institution strives to achieve objectives, which are broader in nature. This is because, not only does it aim at providing the society with financial security, but it also, as a whole, inculcates moral, social and spiritual values in each individual. In view of the institution of Zakat aiming at achieving broader objectives, this research therefore, seeks to prove that the institution of Zakat may not only form the basis of today’s modern social security system, but also brings some other benefits to the society. The whole research however, is divided into several sub-sections besides a conclusion. It therefore, presents the foundation of the institution of Zakat followed by the evaluation of whether the institution of Zakat can provide a meaningful social security along with a justification that, the institution of Zakat is capable of providing a result oriented alternative to the modern social security system. Keywords: Zakat, poverty eradication, sustainability, social securityJEL Classification Code: E62, H21,P51